The discourse on learning styles in online education - Idrizi, Ermira; Filiposka, Sonja; Trajkovikj, Vladimir (IEEE, 2019)
Online learning is a contemporary concept in which ideas, models, and traditional teachings have changed. We examine how learning style affects the learner’s academic achievements in online lessons and gender-specific environments. This research investigates whether VARK styles are associated with course results, regardless of the actual VARK results, and whether any study techniques are associated with course results. The results indicate that almost all students did not report on research approaches after their VARK assessment and that the students' achievement is not associated with their results in each VARK category. This provides additional evidence that the usual teaching styles should be redefined for Online classes where the styles corresponding to the willingness of learners are more difficult to be defined.
Keywords: Gender, Online Learning, VARK learning styles